Electroglottography in the hearing impaired - Manjula P (Journal of All India Institute of Speech and Hearing, 1970)
Deafness, even profound deafness, does not prevent an individual from producing voice. However, the loss of hearing does affect the control of voice production and when people listen to the speech of a deaf person, a typical reaction is that the speaker's voice sounds ' abnormal'" (Monsen et al, 1979).